How Does the Dramatic Rise of CPS Non-Response Impact Labor Market Indicators? - Robert Bernhardt; David Munro; Erin Wolcott (Global Labor Organization (GLO), 2021)
Since 2010 and before the pandemic hit, the share of households refusing to participate in the Current Population Survey (CPS) tripled. We show that partially-responding households - households that respond to some but not all of the survey's eight panels - account for most of the rise. Leveraging the labor force status of partially-responding households in the months surrounding their non-response, we find that rising refusals artificially suppressed the labor force participation rate and employment-population ratio but had little discernible effect on the unemployment rate. Factors robustly correlated with state-level refusal rates include a larger urban population, a smaller Democratic vote share (our proxy for sentiment towards government), and the economic and social changes brought about by manufacturing decline.
Keywords: C83; E24; J64; 330; Current Population Survey; Non-Response; Unemployment; Labor Force Participation; Employment-Population Ratio